IMPLEMENTASI APLIKASI E-BUKTI POTONG PAJAK PENGHASILAN DALAM RANGKA EFISIENSI PEMENUHAN KEWAJIBAN PERPAJAKAN PADA PT ENERGY UTAMA ALAM MULIA (Jurnal Ekonomi : Journal of Economic, 2022)
In Indonesia, every citizen and business actor has the same rights and obligations in taxation. According to the Director General of Taxes Decree No. KEP-368/PJ/2020, tax transactions on Article 23 and/or Article 26 income can be carried out using E-Bupot (Electonic Proof of Tax Withholding). The purpose of this study was to determine and analyze the implementation of the E-Bupot application on Article 23/26 income at PT Energy Utama Alam Mulia as well as the obstacles and efforts made in the context of efficient fulfillment of tax obligations. This research used descriptive qualitative method. The results show that the implementation of E-Bupot using indicators of communication, resources, disposition, and bureaucratic structure is in accordance with tax regulations in the reporting process, there are obstacles, namely payments and the data upload process. Efforts made to overcome these obstacles logging into the profile, activating features, checking the e-bupot Income Tax Article 23/26 for Period Tax Return reporting, entering the report menu at the online DGT then selecting Pre reporting and selecting e-bupot Income Tax article 23/26.